Proteomic analysis in primary T cells reveals IL-7 alters T cell receptor thresholding via CYTIP/cytohesin/LFA-1 localisation and activation. Issue 3 (11th February 2022) - Queiroz, Rayner M. L.; Piper, Siân C.; Rees, Johanna S.; Strickson, Sam; Briend, Emmanuel; Low, Choon Pei; Ferguson, G. John; Lilley, Kathryn S.; Jackson, Antony P.; Finch, Donna K.
Abstract : The ability of the cellular immune system to discriminate self from foreign antigens depends on the appropriate calibration of the T cell receptor (TCR) signalling threshold. The lymphocyte homeostatic cytokine interleukin 7 (IL-7) is known to affect TCR thresholding, but the molecular mechanism is not fully elucidated. A better understanding of this process is highly relevant in the context of autoimmune disease therapy and cancer immunotherapy. We sought to characterise the early signalling events attributable to IL-7 priming; in particular, the altered phosphorylation of signal transduction proteins and their molecular localisation to the TCR. By integrating high-resolution proximity- phospho-proteomic and imaging approaches using primary T cells, rather than engineered cell lines or an in vitro expanded T cell population, we uncovered transduction events previously not linked to IL-7. We show that IL-7 leads to dephosphorylation of cytohesin interacting protein (CYTIP) at a hitherto undescribed phosphorylation site (pThr280) and alters the co-localisation of cytohesin-1 with the TCR and LFA-1 integrin. These results show that IL-7, acting via CYTIP and cytohesin-1, may impact TCR activation thresholds by enhancing the co-clustering of TCR and LFA-1 integrin.